Equity yields - van Binsbergen, Jules; Hueskes, Wouter; Koijen, Ralph; Vrugt, Evert (Journal of Financial Economics, 2013)
We study a new data set of dividend futures with maturities up to ten years across three world regions: the US, Europe, and Japan. We use these asset prices to construct equity yields, analogous to bond yields. We decompose the equity yields to obtain a term structure of expected dividend growth rates and a term structure of risk premia, which decomposes the equity risk premium by maturity. We find that the slope of the term structure of risk premia is pro-cyclical, whereas the slope of the term structure of expected dividend growth rates is counter-cyclical. The comovement of yields across regions is, on average, higher for long-maturity yields than for short-maturity yields, whereas the variation in this comovement is much higher for short-maturity yields.